A 22 GHz water maser radiometer - Nunn, Brian J (Rhodes University, Faculty of Science, Department of Physics, 1975)
This thesis describes the properties of interstellar water maser sources, and other sources near 22 GHz. Calculations based on manufacturer's specifications of the 22 GHz mixer, which was to be used in a water radiometer, and on the size antenna aperture of the proposed antenna aperture, show the viability of constructing such a radiometer for spectral line and continuum work. Various sections of the radiometer were constructed, including the Cassegrain feed system and its support, an intermediate frequency amplifier and buffer, a timing control unit, and a data processor. These units are part of the radiometer, which is almost ready for observations of sources.
Keywords: Masers; Radiometers